Mindful pregnancy : meditation, yoga, hypnobirthing, natural remedies, nutrition : trimester by trimester - Donegan, Tracy (DK Publishing, 2020)
Trimester by trimester, this beautiful book gives you safe yoga, meditation, natural remedies, nutrition, and hypnobirthing techniques to match your stage of pregnancy. Encouraging, practical advice from midwife and positive birth expert, Tracy Donegan, will help you to understand your body, relish your pregnancy, and bond with your growing baby. Feel empowered to nurture and give birth to your baby with strength and confidence, and embrace your life as a new mother.